Kajian Produksi Karkas Dan Non Karkas Ayam Kampung Dengan Pemberian Ransum Komersial Tersubstitusi Tepung Kulit Biji Kedelai - Sari Sari; Harapin Hafid; Andi Murlina Tasse (Universitas Halu Oleo, 2016)
ABSTRACTThe study was conducted to find out the effect of fed commercial ration substituted soybean shell meal (SSM) on native chickens carcass and non carcass weight and percentage. Sixteen native chicken aged 7 weeks and was treatmented T0 (0% SSM), T1 (10% SSM), T2 (20% SSM) and T3 (30% SSM) each. 4 chickens. The study used a completely randomized design (CRD). Data obtained were analyzed using a analysis of variance (ANOVA) and then was continued with Duncans multiple range test (DMRT). Results of the study showed that slaughter weights (SW, g/chicken) are highest 529.0 (T2) followed with 484.0 (T3), 452 (T1) and lowest 402.0 (T0). Carcass Weights (CW, g/chicken) are highers 421.50 (T2), followed with 370.75 (T3), 331.50 (T1) and lowest 285.50 (T0). Carcass percentages (CP, %) are highest 76.69 (T2), 76.64 (T3) followed with 73.39 (T1), 71.42 (T0). Non carcass weights (NCW, g/chicken) 116.50-113.25 (T0-T3) and non carcass percentage (NCP, %) are highest 26.68 (T1), 25.58 (T0), 23.36 (T3) and lowest 20.31 (T2). Gizzard weights (GW, g/chicken) are 14.00 (T0), 18.00 (T1), 17.50 (T2) and 14.50 (T3). Gizzard percentages (GP, %) are 3.71 (T0), 3.99 (T1), 3.31 (T2) and 3.00 (T3). Liver weights (LW, g/chicken) are 12.00 (T0), 13.50 (T1), 15.00 (T2) and 12.00 (T3). Liver percentages (LP, %) are 2,98 (T0), 2,97 (T1), 2.85 (T2) and 2.48 (T3). Heart weights (HW, g/chicken) was 2.00 (T0), 2.00 (T1), 2.50 (T2) and 2.00 (T3). Heart percentages (HP,%) are 0.50 (T0), 0.45 (T1), 0,47 (T2) and 0.42 (T3). The conclusion of the study that fed commercial ration substituted soybean shell meal improved carcass performa but non significantly influence non carcass (viscera) performance native chicken. Key words: soybean, shell meal, carcass, non-carcass, viscera, native chicken